Road Traffic Accidents with Head Injury: A Study from Western Uttar Pradesh - Urfi; Samia Kirmani; Ali Amir; Mohd. Fakhrul Hoda; Salman Khalil (Medsci Publications, 2013)
Background: Head is the most vulnerable part of the body to be fatally injured in road traffic accidents (RTAs). Objective: To study the distribution and severity of road traffic accidents with head injury according to type of transport and road user.  Methods: A hospital based cross-sectional study was conducted in casualty and allied departments of JNMC, Aligarh. All admitted cases of RTA with head injury in the age-group 15-45 years from August 2010 to July 2011 were included in the study using purposive sampling. Results: A total of 463 cases of road traffic accident with head injuries were studied. Most common transport used was two wheeler motorized vehicle (73.7%). Majority (58.1%) of road users were driving the vehicle. Conclusion: Two wheeler motorized vehicles are at increased risk of RTA leading to head injury.